The prevalence of Schistosoma mansoni infection among adults with chronic non-communicable diseases in Malawi - Wongani Nyangulu; Christina Sadimba; Joyce Nyirenda; George Twaibu; John Kamwendo; Kelvin Chawawa; Angella Masano; Elizabeth Chilinda; Sekeleghe Kayuni; Adamson S. Muula; Kenneth Maleta (Tropical Medicine and Health, 2022)
Abstract Background Schistosomiasis is a parasitic infectious disease caused by flatworms of the Schistosoma genus. The global burden of schistosomiasis is high. In Malawi, schistosomiasis is among the top 20 causes of outpatient department visits in health facilities. Schistosomiasis is among the most important but neglected causes of non-communicable diseases (NCD) peculiar to tropical endemic settings. While much is known about the contribution of S. haematobium to the NCD burden in Malawi, the role of S. mansoni remains largely unknown. Methods We conducted a cross-sectional study at Mangochi District Hospital. Adults over 18 years diagnosed with NCDs (n = 414), admitted or attending weekly outpatient clinics were recruited between August 2021 and February 2022. Data were collected on sociodemographic characteristics, medical history, body weight, blood pressure, and fasting blood glucose. Stool and midstream urine were collected for Kato–Katz (KK) microscopy and urine point of care-circulating cathodic antigen (POC-CCA) tests, respectively. We computed prevalence of S. mansoni as number of positive KK and CCA tests, each divided by total submitted samples. Univariate and multivariable logistic regression were done to evaluate risk factors of NCDs and association between S. mansoni infection and NCDs. Results We recruited 414 participants, mean age 57 years (SD 16), 67% of whom were female. Prevalence of S. mansoni based on urine CCA was 15% (95% CI: 11–19) and 0% on KK microscopy. Hypertension was the most common condition with a prevalence of 85% (95% CI: 81–89), followed by diabetes mellitus with a prevalence of 42% (95% CI: 37–46) and heart disease with a prevalence of 3% (95% CI: 2–5). S. mansoni infection was not significantly associated with hypertension (OR: 1.2, 95% CI: 0.5–3.1), diabetes (OR: 0.6, 95% CI: 0.3–1.10) or heart disease (OR: 2.0, 95% CI: 0.4–10). Conclusions We observed moderate prevalence of S. mansoni infection among adults in the study per WHO classification of endemicity. This is within the range observed in children in Mangochi from 10 to 56.7%.